Family resilience processes among guardians caring for children and youths with leukemia - Surangkana Suparit; Nanchatsan Sakunpong; Thasuk Junprasert (Heliyon, 2023)
Based on Walsh's concept of family resilience, this study aims to explain the processes and factors related to family resilience of guardians caring for children and youths with leukemia (GCYL) at a university-affiliated hospital in central Thailand. An explanatory case study is conducted. Semi-structured in-depth interviews were conducted with 21 guardians from 15 families caring for children and youths with leukemia (CYL). The interviews were recorded and transcribed for content analysis. The researcher categorized and coded the data to summarize, interpret, and validate the key study results of family resilience.This study found that families undergo three phases when facing the situation: pre-family resilience, family resilience, and post-family resilience. In each phase, these families face changes in emotions, perspectives, and behaviors related to the factors promoting family resilience. The results of this study will benefit multidisciplinary teams providing care for families with CYL by applying the information about family resilience processes to provide services that cultivate behavioral, physical, psychological, and social growth for the families and enable them to maintain peace in family life.